Olfactory dysfunction amongst children and adolescents with laboratory confirmed coronavirus disease 2019: a systematic review. Issue 11 (2nd November 2021) - Saniasiaya, J; Kulasegarah, J; Narayanan, P
Abstract: Background: Despite the rapidly emerging reports of olfactory dysfunction amongst adult patients with coronavirus disease 2019, cases involving children and adolescents are scarcely reported. The literature was reviewed to elucidate olfactory dysfunction amongst children and adolescents with coronavirus disease 2019. Methods: A search of the literature published from 1 December 2019 to 30 April 2021 was conducted using four databases, based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and the Cochrane Handbook for Systematic Reviews of Interventions. The search was performed over one month (May 2021). Results: Only 9 articles were identified, with a total of 316 laboratory confirmed coronavirus disease 2019 positive children and adolescents, of whom 156 reported olfactory dysfunction. Four studies reported olfactory dysfunction based on subjective tests; four studies carried out objective assessment. Most studies reported on olfaction recovery. Conclusion: The literature review revealed an olfactory dysfunction rate of 49 per cent amongst children and adolescents with coronavirus disease 2019. Persistence of olfactory dysfunction was reported in 7.1 per cent of the patients. Further studies involving objective measures need to be carried out in children and adolescents with coronavirus disease 2019.